Platelet-rich plasma combined with isometric quadriceps contraction regulates autophagy in chondrocytes via the PI3K/AKT/mTOR pathway to promote cartilage repair in knee osteoarthritis - Liang Cheng; Shuwan Chang; Yajun Tan; Benxiang He (Regenerative Therapy)
Background: This study investigated the molecular mechanism by which the combination of platelet-rich plasma (PRP) and isometric contraction of the quadriceps (ICQ) intervention regulates autophagy in chondrocytes to prevent and treat knee osteoarthritis (KOA). Methods: Thirty Sprague-Dawley rats were divided into a control group (CG, n = 6) and a model group (n = 24). After one week, the model group was randomly divided into a joint intervention group (JIG), a rapamycin group (RAG), an MHY1485 group (MYG), and a model blank group (MBG), with JIG, RAG, and MYG receiving the same combined intervention. Results: The trend of cartilage lesions in each group was CG < RAG < JIG < MYG < MBG. Compared with MBG and MYG, JIG and RAG showed downregulation of IL-1β, IL-6, IL-18, MMP-13, and TNF-α mRNA in the cartilage (p < 0.01); mTOR protein expression: compared with JIG, RAG showed downregulation, and MYG showed upregulation. Compared with RAG, MYG showed upregulation (p < 0.01); ATG5 protein expression: compared with RAG, MYG showed downregulation (p < 0.01); Beclin1, LC3-I, and ULK1 protein expression: compared with JIG, RAG showed upregulation, and MYG showed downregulation (p < 0.01). Compared with RAG, MYG showed downregulation (p < 0.01); P62 protein expression: compared with RAG, both MBG and RAG showed upregulation, and MYG showed downregulation (p < 0.05); LC3-II/LC3-I ratio: compared with JIG and RAG, the ratio in MYG was decreased (p < 0.01). Conclusion: The combined intervention promotes autophagy in chondrocytes by inhibiting the PI3K/AKT/mTOR pathway, downregulating inflammatory factors and MMP-13 in the cartilage, upregulating autophagy markers, inhibiting matrix degradation, and promoting cartilage repair.